Tumor perfusion enhancement by microbubbles ultrasonic cavitation reduces tumor glycolysis metabolism and alleviate tumor acidosis - Qiu, Danxia; He, Yangcheng; Feng, Yuyi; Lin, Minhua; Lin, Zekai; Zhang, Zhiyi; Xiong, Ying; Hu, Zhiwen; Ma, Suihong; Jin, Hai; Liu, Jianhua (Frontiers in Oncology, 2024)
The tumor microenvironment is increasingly acknowledged as a critical contributor to cancer progression, mediating genetic and epigenetic alterations. Beyond diverse cellular interactions from the microenvironment, physicochemical factors such as tumor acidosis also significantly affect cancer dynamics. Recent research has highlighted that tumor acidosis facilitates invasion, immune escape, metastasis, and resistance to therapies. Thus, noninvasive measurement of tumor acidity and the development of targeted interventions represent promising strategies in oncology. Techniques like contrast-enhanced ultrasound (CEUS) can effectively assess blood perfusion, while ultrasoundstimulated microbubble cavitation (USMC) has proven to enhance tumor blood perfusion. We therefore aimed to determine whether CEUS assesses tumor acidity and whether USMC treatment can modulate tumor acidity. Firstly, we tracked CEUS perfusion parameters in MCF7 tumor models and compared them with in vivo tumor pH recorded by pH microsensors. We found that the peak intensity and area under curve of tumor contrast-enhanced ultrasound correlated well with tumor pH. We further conducted USMC treatment on MCF7 tumor-bearing mice, tracked changes of tumor blood perfusion and tumor pH in different perfusion regions before and after the USMC treatment to assess its impact on tumor acidity and optimize therapeutic ultrasound pressure. We discovered that USMC with 1.0 Mpa significantly improved tumor blood perfusion and tumor pH. Furthermore, tumor vascular pathology and PGI2 assays indicated that improved tumor perfusion was mainly due to vasodilation rather than angiogenesis. More importantly, analysis of glycolysis-related metabolites and enzymes demonstrated USMC treatment can reduce tumor acidity by reducing tumor glycolysis. These findings support that CEUS may serve as a potential biomarker to assess tumor acidity and USMC is a promising therapeutic modality for reducing tumor acidosis.